The Effect of Jump to Box Training towards Triple Jump Ability at SMA Negeri 2 Bungo - Dwiwinanda, Prandi (The Future of Education Journal, 2023)
This research is a quantitative research with experimental method with the research design used is "one groups pretest-posttest design". This study aims to determine the effect of the Jump to Box exercise on the triple jump ability at SMA Negeri 2 Bungo. The population in this study were all male students of class XII who were at SMA Negeri 2 Bungo with several criteria, so the number of samples in this study were 30 male students of class XII. The instrument in this study was the triple jump test by being given the Jump to Box exercise. The results of the study concluded that there was an effect of jump to box training on the ability to triple jump at SMA Negeri 2 Bungo, with t count (37.12) > t table (1.699) at a significance of 5%. This means that Ha is accepted which explains that there is a positive influence between the jump to box exercise on the triple jumping ability of Bungo 2 Public High School students with a large correlation (r) of 0.99. The value of r is interpreted to mean a very strong influence, and the coefficient of determination is 0.992 which is 98%, meaning that the jump to box exercise affects 98% of the triple jump ability of students at SMA Negeri 2 Bungo, more than 2% is influenced by other factors